Review of Indonesian species of the leafhopper genus Drabescus Stål (Hemiptera: Cicadellidae: Deltocephalinae) with description of two new species - Xu, Deliang; Zhang, Yalin (Zootaxa, 2018)
Two new species Drabescus stilliformis and D. viraktamathi spp. nov., are described and illustrated from Indonesia. A checklist and key to males from Indonesia are provided. Type specimens of the new species are deposited in the Natural History Museum, London, U.K. (BMNH) and the National Museum of Wales, Cardiff, U.K. (NMW).